Level of Local Community Brand Awareness of Samosir Tourism - Nur Cahaya Bangun; Jhonson Pardosi; Ilham Mirzaya Putra (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This study aims to: (1) determine the level of local community brand awareness of the brand